2016
DOI: 10.1186/s12865-016-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of storage temperature on PBMC gene expression

Abstract: BackgroundCryopreservation of peripheral blood mononuclear cells (PBMCs) is a common and essential practice in conducting research. There are different reports in the literature as to whether cryopreserved PBMCs need to only be stored ≤ −150 °C or can be stored for a specified time at −80 °C. Therefore, we performed gene expression analysis on cryopreserved PBMCs stored at both temperatures for 14 months and PBMCs that underwent temperature cycling 104 times between these 2 storage temperatures. Real-time RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…Nevertheless, our study provided evidence that minimal change in temperature did not disturb LCE1D gene expression. Our results augmented the findings of Yang et al (2016), who also reported that different storage temperatures could activate or suppress different genes. However, such temperature changes did not show any significant alterations in gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, our study provided evidence that minimal change in temperature did not disturb LCE1D gene expression. Our results augmented the findings of Yang et al (2016), who also reported that different storage temperatures could activate or suppress different genes. However, such temperature changes did not show any significant alterations in gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…The density gradient separation principle was first described by Böyum A. [30,31] and quickly became the most popular PBMC preparation method. A major advantage of this method for lymphocyte immunophenotyping is the removal of most erythrocytes, granulocytes and nonvi- able cells from the sample [17].…”
Section: Discussion Density Gradient Centrifugation -Advantages and Lmentioning
confidence: 99%
“…However complexities exist in this analysis (Figure 1), particularly when considering use of archival versus fresh tissue. First, cryopreservation has been shown to alter certain immune cell subsets and cytokine profiles [1] as well as gene expression profiles [2] when assessing immune cell function in tumors and blood by flow cytometry, rendering this information less reliable compared to fresh tissue. Similarly, comparison of whole exome sequencing (WES) – important for determination of mutational burden and neoantigen prediction - in archival versus paired fresh tissue shows that genomic variants are lost by using formalin fixed paraffin embedded (FFPE) tissue [3].…”
Section: Clinical Challenges Of Immune Monitoringmentioning
confidence: 99%